Deixis’s Analysis of Atouna El Toufoule’s Song on George Yule’s Perspective - Bariyyah, Isnaeni Khoirul; Dienana, Arina; Sopian, Asep; Fauziyah, Widad Nur (Linguistic, English Education and Art (LEEA) Journal, 2024)
Songs help share messages in different ways. Besides being artistic, they also carry values and messages from the singer through their lyrics. Some songs use simple sentences to make the message clear to listeners. Songs aren’t just for fun, they also deliver different messages. In this research, the song Atouna el Toufoule will be analyzed and classified into three types of deixis using George Yule’s theory, then correlated with phenomena that occur in connection with the song and expressed the optimistic values ​​contained in the song. In this research, the song Atouna el Toufoule will be analyzed and classified into three types of deixis using George Yule’s theory. It will then be correlated with phenomena that occur in connection with the song and express the optimistic values ​​contained in the song. The qualitative descriptive method is used in this research, and a content analysis research design is applied. After analysis, the deixis contained in the song Atouna el Toufoule are 36 persona deixis, 0 place deixis and 1 time deixis, persona deixis is dominant in this song. By examining parts of the lyrics from Atouna el Toufoule song we can see the songwriter narrating the sorrowful and ironic experiences children face, particularly those affected by war. This research not only looks at deixis but also correlates the song's lyrics to the grim reality of children losing their childhood to war while also highlighting the message of optimism embedded in each lyric. Bottom of Form Keyword: Atouna el Toufuole, Deixis, Optimism, Pragmatics